1955
DOI: 10.1136/bjo.39.4.220
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Supply of the Optic Pathway : II. Further Studies by Micro-Arteriography of the Optic Nerve

Abstract: and the institute of Radiology, University ofLiege (Director, Prof. Leroux) THE literature gives few details of the intimate vascularization of the optic pathway. Leber (1903) found in the optic nerve a vascular network, composed of round meshes; he described other vessels running obliquely along the whole length of the optic nerve, which became smaller with more closely woven meshes at the level of the lamina cribrosa.Wolff (1948) agreed with Leber that the distribution of the septa containing the vessels be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1955
1955
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Collaterals from both the longitudinal and transverse units join to form a complicated capillary plexus. The angioarchi tecture in the region of the lamina cribrosa has been de scribed as comprising numerous, small, very close and transversely elongated meshes [39,40] and is very dense [41][42][43]. In my studies, I found that in the retrolaminar re gion the longitudinal and transverse capillaries formed a complicated meshwork, in the lamina cribrosa the capillar ies were arranged mostly transversely, like the connective tissue septa there, and in the prelaminar region the arrange ment was like that in the retrolaminar region [23], The peri papillary choriocapillaris does not anastomose with the cap illary plexus in the prelaminar region.…”
Section: Variations In the Pattern Ofpca Circulationmentioning
confidence: 99%
“…Collaterals from both the longitudinal and transverse units join to form a complicated capillary plexus. The angioarchi tecture in the region of the lamina cribrosa has been de scribed as comprising numerous, small, very close and transversely elongated meshes [39,40] and is very dense [41][42][43]. In my studies, I found that in the retrolaminar re gion the longitudinal and transverse capillaries formed a complicated meshwork, in the lamina cribrosa the capillar ies were arranged mostly transversely, like the connective tissue septa there, and in the prelaminar region the arrange ment was like that in the retrolaminar region [23], The peri papillary choriocapillaris does not anastomose with the cap illary plexus in the prelaminar region.…”
Section: Variations In the Pattern Ofpca Circulationmentioning
confidence: 99%
“…Instead of preparing brief abstracts and an interminable bibliography, I have preferred to be selective and devote the space to significant articles. 4. Not all patients showed field defects.…”
mentioning
confidence: 97%
“…The future will probably teach us ¡that it is not a matter of superiority of one method over the other but that each method has its merits in the detection of certain types of defects, and that the two methods are complementary rather than com¬ petitive. 4. Harrington and Hoyt2 report their success in detecting a central scotoma in this situation by the use of ultraviolet radiation and luminescent mon¬ ochromatic blue test objects under partially scotopic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The rest, as they say, is history. The original object of my study was to prove the existence of the central artery of the optic nerve, claimed by Francois et al .,[ 2 3 ] but I ended up proving that the artery did not exist and investigating the entire vascular bed of the orbit, optic nerve, and the eye in detail. The central retinal artery component of my work was accepted as my thesis for the Master of Surgery (equivalent to the American Board) by the Punjab University.…”
mentioning
confidence: 99%